(3aJM GdhgGH HTQM efgL GdWdGHs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s
(3ChdgG (B:s
(3GfbVGFg hdh bHd MjGRI GdeGd hdG def MVQhG s
(3BNQgG (B:s
(3hChUi HYJbgG ef GdKdK cEfaGbg GdeGd ai GdTghGJ hbO Je GdcJGH GdeSei aJM GdhgGH HTQM efgL GdWdGH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B374s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1875s
Keywords: (3GdQjGVjGJs